Insignificant difference in culture conversion between bedaquiline-containing and bedaquiline-free all-oral short regimens for multidrug-resistant tuberculosis - Fu, Liang; Weng, Taoping; Sun, Feng; Zhang, Peize; Li, Hui; Li, Yang; Yang, Qianting; Cai, Yi; Zhang, Xilin; Liang, Hancheng; Chen, Xinchun; Wang, Zhaoqin; et al. (International journal of infectious diseases, 2021)
•The first trial to explore all-oral short regimens for MDR-TB in China.•Two optimized regimens, designed according to local conditions.•Similar high culture conversion in the early stage in both regimens.•High treatment success rate for patients who completed the treatment.•Good adherence in the pandemic of COVID-19. Multidrug-resistant tuberculosis (MDR-TB) patients have been suffering long, ineffective, and toxic treatment until short-course injectable-free regimens emerged. However, the new WHO-recommended regimens might be less feasible in the real-world setting. Here, we evaluated two optimized all-oral short-course regimens in China. From April 2019 to August 2020, we conducted a prospective nonrandomized controlled trial and consecutively included 103 MDR-TB patients diagnosed with pulmonary MDR-TB in Shenzhen, China. A 4-5 drug regimen of 9-12 months was tailored to the strain's resistance patterns, patients' affordability, and tolerance to drugs. This was an interim analysis, focusing on the early treatment period. 53.4% (55/103) of patients were prescribed linezolid, fluoroquinolone (FQ), clofazimine, cycloserine, and pyrazinamide, followed by a regimen in which clofazimine was replaced by bedaquiline (35/103, 34.0%). The culture conversion rate was 83.1% and 94.4% at two and four months, respectively, with no significant difference between bedaquiline-free and bedaquiline-containing cases and between FQ-susceptible and FQ-resistant cases. Among 41 patients who completed treatment, 40 (97.6%) patients had a favorable outcome and no relapse was observed. Peripheral neuropathy and arthralgia/myalgia were the most frequent AEs (56.3%, 58/103). 18 AEs caused permanent discontinuation of drugs, mostly due to pyrazinamide and linezolid. Optimized all-oral short-course regimens showed satisfactory efficacy and safety in early treatment stage. Further research is needed to confirm these results.